Penolakan Pemberian Rekomendasi Pembebanan Hak Tanggungan Terhadap Hak Guna Bangunan di atas Hak Pengelolaan Pemerintah Kalimantan Timur - Amalia, Diera Ajeng (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2018)
The aim of the study was to find out the misinterpretation in the East Kalimantan Government in the gubernatorial letter number: 593/5102 / BP-II / VI / 2012 concerning the reasons for refusing to provide recommendations for the guarantee of Underwriting Rights on Building Use Rights over the Government's East Kalimantan Management Rights. The research method used normative research (Statue Approach, legal concept analysis and Case Approach. The results of the study indicate the occurrence of misinterpretations in the Letter of the Governor of East Kalimantan Number: 593/5102 / BP-II / VI / 2012, in which the East Kalimantan Government as the Management Right holder refused to provide written recommendations or approval to the Building Use Rights owners, namely Housing residents Korpri Samarinda based on the provisions of Law Number 1 of 2004 concerning State Treasury in Article 49 paragraph (5) which states that "State / Regional Property is prohibited from being mortgaged or used as collateral for obtaining loans" is inappropriate. Because what the residents of the Samarinda Korpri Housing want to pledge is that the building is not the land where the building is a private property, keeping in mind the principle of horizontal separation in the Indonesian agrarian law. Tujuan Penelitian adalah mengetahui kesalahan tafsir di dalam Pemerintah Kalimantan Timur dalam surat gubernur nomor : 593/5102/BP-II/VI/2012 mengenai alasan menolak memberikan rekomendasi guna penjaminan Hak Tanggungan atas Hak Guna Bangunan diatas Hak Pengelolaan milik pemerintah Kalimantan Timur. Metode penelitian menggunakan metode penelitian normatif (The Statue Approach), pendekatan analisa konsep hukum (Analitical & Conseptual Approach), dan pendekatan kasus (Case Approach). Hasil penelitian menunjukan Terjadinya salah tafsir di dalam Surat Gubernur Kalimantan Timur Nomor: 593/5102/BP-II/VI/2012, yang mana Pemerintah Kalimantan Timur sebagai pemegang Hak Pengelolaan menolak untuk memberikan rekomendasi atau persetujuan tertulis terhadap pemilik Hak Guna Bangunan yaitu warga Perumahan Korpri Samarinda dengan berdasar dalam ketentuan Undang-Undang Nomor 1 Tahun 2004 tentang Perbendaharaan Negara adalah kurang tepat. Karena yang ingin diagunkan oleh warga Perumahan Korpri Samarinda adalah bangunannya yang merupakan hak milik pribadi, dengan mengingat asas pemisahan horizontal yang berlaku dalam hukum agraria Indonesia.